Financial Accessibility, Business Development, and the Economic Welfare of MSMEs in Rural Indonesia - Rasyidi, Ahmad Hafas; Dassucik, Dassucik (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study examines how capital structure and KUR accessibility influence the economic welfare of Micro, Small, and Medium Enterprises (MSMEs). It contributes to MSME financing research by extending the Resource-Based View (RBV), positioning financial accessibility as a strategic internal capability that drives business development and resilience. Using survey data from 130 MSME owners analyzed with SmartPLS 4.0, the study finds that both capital structure and financing accessibility significantly affect business development, which mediates their impact on economic welfare. Microcredit program (KUR) plays a vital role in reducing financial constraints and promoting firm growth. The results underscore that strengthening financial inclusion and managing financial resources strategically are essential to sustaining MSME competitiveness and long-term economic growth.